Perception of Divorced Mothers on the Role of Father's Involvement in Child Emotional Regulation with Coparental Interaction as Moderator - Hariadi, Hariadi; Satiadarma, Monty P.; Roswiyani (Universitas Medan Area, 2024)
When parents divorce, fathers are often less involved in parenting. Whereas one of the factors that can affect the ability of emotion regulation in children and adolescents is father involvement in parenting. This study aims to determine the relationship between father involvement and emotion regulation of children and adolescents which is moderated by coparental interaction. Coparental interaction is how a divorced couple is involved in raising children together even though their marriage relationship has ended. The participants of this study were 330 divorced women, who had children aged ranging from 2-18 years. Data collection used three measurement tools, namely the Father Engagement, the Emotion Regulation Checklist (ERC), and the Coparenting Scale for Dissolved Relationships (MCS-DR). The results show that Coparental interaction acts as a moderator in the relationship between father involvement and emotion regulation. This study provides evidence that coparental interaction can increase father involvement in parenting which has an impact on children's emotion regulation. Implementing programs that can maintain a pattern of mutually supportive and cooperative relationships in divorced couples can reduce the impact of divorce on children.